Exploring a meaningful learning intervention in a CS1 course - Josko, João Marcelo Borovina (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.232047, 2023)
Meaningful learning is when students actively integrate new knowledge into their mental structures with purpose and emotion. While previous CS1 literature has explored ideas of meaningful learning, no studies have examined the specific aspects that emerge from students’ learning processes during meaningful learning-driven interventions. To address this gap, we conducted an exploratory case study. We asked 32 students to keep learning journals to document their experiences in a CS1 course designed with a meaningful learning framework. We analyzed the journals qualitatively and found that students adopted the protagonist role in their learning process thanks to a network of influences stemming from the elements introduced in our intervention.